Interrelation between the parameters of endogenous vascular regulation, oxidative stress and the markers of inflammatory response in COVID-19 patients while on extracorporeal membrane oxygenation - E. V. Klychnikova; S. V. Zhuravel; I. V. Ivanov; O. V. Nikitina; E. V. Tazina; A. Yu. Bulanov; A. M. Talyzin; K. A. Popugaev; V. V. Vladimirov; S. S. Petrikov; A. S. Bogdanova (Трансплантология (Москва))
Introduction. Extracorporeal membrane oxygenation has found wide application in clinical practice during the COVID-19 pandemic. Oxidative stress, endothelial dysfunction, and systemic inflammatory response syndrome play an important role in the pathogenesis of COVID-19. Our research was designed to study correlations in-between those factors and the impact of extracorporeal membrane oxygenation on them.Aim. The study of systemic inflammatory response and endothelial function in patients with COVID-19 during extracorporeal membrane oxygenation.Material and methods. In the course of a prospective study, we examined 100 COVID-19 patients aged 26 to 75 years, median 55 years [47;60], who were treated at the N.V. Sklifosovsky Research Institute for Emergency Medicine, using extracorporeal membrane oxygenation. As a control group (normal), 25 practically healthy people whose median age was 32 years [25;39] were examined. The function of the vascular endothelium was assessed by the content of nitric oxide stable metabolites in the blood serum and the level of angiotensin-converting enzyme. Next, the ratio of nitric oxide metabolite to angiotensin-converting enzyme level was calculated, reflecting the imbalance between endotheliumdependent vasodilation and vasoconstriction. To assess the severity of oxidative stress in blood serum, malondialdehyde was determined as a marker of lipid peroxidation. The state of the antioxidant system was assessed in terms of total antioxidant status of blood serum. The presence of an imbalance in the system of lipid peroxidation and the antioxidant system total antioxidant status was judged by the oxidative stress coefficient, i.e. the ratio of malondialdehyde to the total antioxidant activity.Results. The analysis showed the presence and progression of endothelial dysfunction, impaired vascular regulation, activation of free radical processes, the presence of an imbalance in the prooxidant/antioxidant system, as well as the progression of the inflammatory process with a decrease in the level of markers of the COVID-19 severity.Conclusion. Further studies of the correlation between endothelial damage and the severity of the systemic inflammatory response syndrome may be of fundamental importance for explaining the pathophysiological mechanisms of COVID-19 course and developing new treatments for such patients.